Level of hesitation of parents about childhood vaccines and affecting factors: a cross-sectional study in Turkey - Vasfiye BAYRAM DEĞER; Gülhan YİĞİTALP (BMC, 2024)
Abstract Background Hesitancy rates for childhood vaccines are increasing on a global scale. It was reported in previous studies that many factors affect vaccine hesitancy. The present study was designed to determine the prevalence of childhood vaccination hesitancy in parents and to determine the factors affecting it. Methods This descriptive, cross-sectional study was conducted with 350 parents who had at least one child aged two years and younger, who applied to Family Health Centers in the city of Mardin in the Southeastern Anatolia Region of Turkey, between January and March 2022. The "Parental Attitudes Towards Childhood Vaccines (PATCV) Questionnaire" was used to collect the data, which were analyzed by using the SPSS (Statistical Package for Social Sciences) for Windows 22.0 program. The Logistic Regression Analysis was used to determine the factors affecting parental attitudes toward childhood vaccines. Results A total of 32.0% of the parents were found to be hesitant about vaccinations and 3.4% did not have at least one vaccination for their children. Significant relationships were detected between income status, education status, thoughts about vaccinations, parents having adult vaccinations, hesitant to have self-vaccination, considering vaccine necessary, and parental attitudes towards childhood vaccinations (p < 0.05). According to the Regression Analysis, parents who had adult vaccinations had reduced hesitation about childhood vaccines 0.506 times (p = 0.032; OR = 0.506; 95%CI = 0.271-0.943). Considering the vaccine necessary reduced the hesitation about childhood vaccines by 0.440 times (p = 0.011; OR = 0.440; 95%CI = 0.234-0.828). Conclusions The hesitations of parents about childhood vaccines were found to be high. The reasons for vaccine hesitancy must be examined in detail and strategies must be developed in this regard.